Microbiota in Gut, Oral Cavity, and Mitral Valves Are Associated With Rheumatic Heart Disease - Shi, Xue-Rui; Chen, Bo-Yan; Lin, Wen-Zhen; Li, Yu-Lin; Wang, Yong-Li; Liu, Yan; Huang, Jing-Juan; Zhang, Wei-Wei; Ma, Xiao-Xin; Shao, Shuai; Li, Ruo-Gu; Duan, Sheng-Zhong (Frontiers in Cellular and Infection Microbiology, 2021)
Rheumatic heart disease refers to the long-term damage of heart valves and results from an autoimmune response to group A Streptococcus infection. This study aimed to analyze the microbiota composition of patients with rheumatic heart disease and explore potential function of microbiota in this disease. First, we revealed significant alterations of microbiota in feces, subgingival plaques, and saliva of the patients compared to control subjects using 16S rRNA gene sequencing. Significantly different microbial diversity was observed in all three types of samples between the patients and control subjects. In gut, the patients possessed higher levels of genera including Bifidobacterium and Eubacterium, and lower levels of genera including Lachnospira, Bacteroides and Faecalibacterium. Coprococcus was identified as a super-generalist in fecal samples of the patients. Significant alterations were also observed in microbiota of subgingival plaques and saliva of the patients compared to control subjects. Second, we analyzed microbiota in mitral valves of the patients and identified microbes that could potentially transmit from gut or oral cavity to heart valves, including Streptococcus. Third, we further analyzed the data using random forest model and demonstrated that microbiota in gut, subgingival plaque or saliva could distinguish the patients from control subjects. Finally, we identified gut/oral microbes that significantly correlated with clinical indices of rheumatic heart disease. In conclusion, patients with rheumatic heart disease manifested important alterations in microbiota that might distinguish the patients from control subjects and correlated with severity of this disease.